Pasang Surut Partisipasi Masyarakat Sipil dalam Pembentukan Kebijakan Publik di Aceh - Afrizal Tjoetra; Cut Asmaul Husna; Samwil Samwil; Raihal Fajri (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
Acehnese Civil Society Organizations have formed policy products, laws, and derivative products, such as the formation of Law Number 11 of 2006 concerning the Government of Aceh. The government started this law after signing an agreement between the Indonesian government and the Free Aceh Movement. However, the public participation has decreased in forming several Qanuns. The study aims to discover why public participation in policy formation in Aceh has decreased the supporting and inhibiting factors. The research was conducted using qualitative methods. Data was collected through literature study and interviews. The research results show the ebb and flow of civil society participation in the formation of public policy: (1) changes in behavior and government institutions, but followed by community apathy due to the lack of feedback on input in the discussion of laws and regulations; (2) increasing the capacity of public institutions or organizations, but followed by a decrease in the number of NGOs that focus on public policy advocacy; (3) ease of public access to information, but no impact on open government management and community welfare; and (4) social changes that support participation of civil society in the formation of laws and regulations. Meanwhile, the results also show the supporting factors, such as the availability of resources and guarantees for fulfilling public rights. The inhibiting factors for ongoing public participation in policy formation consist of the availability of resources, socio-cultural factors, and the lack of feedback or follow-up on public input